Desafios no processo de obtenção da segurança hídrica frente a aplicação dos instrumentos de gestão da água - Ribeiro, Rodrigo Zanelati (2021)
The increased demand for water has aggravated conflicts between different users and about half of the world's population lives in areas of potential water scarcity, for at least one month a year, a percentage that could worsen until 2050. These two pieces of evidence point to dimension of the water crisis on a world scale. The extensive literature on the subject highlights that this crisis is more related to management than to the availability of the resource. In this sense, there are gaps in the understanding and applicability of instruments responsible for supporting the Integrated Water Resources Management process, as well as their importance for Water Security. In this context, the main research’s objective is to characterize the current scenario of Water Security, in an interstate hydrographic basin, as well as the weaknesses of the legal instruments involved in this process. To this end, a risk mapping was drawn up showing the weak points in terms of water security, based on water consumption data, land use and occupation, and water availability in the basin. The study was carried out in the hydrographic basin of the Paranaíba River, due to its socioeconomic importance for the central west region of Brazil. It presents, as main conclusions, the need for the effective application of the management instruments of Law nº 9,433 of 1997, in addition to demonstrating the high risks to water security in regions upstream of large urban centers and, mainly, in regions close to the source of the river Paranaíba. The results found reflect a national reality.